Exploring golden eagle habitat preference using lidar-based canopy bulk density - Warner, Timothy A.; Miller, Tricia A.; La Puma, Inga P.; Nolan, Lee Ann; Skowronski, Nicholas S.; Maxwell, Aaron E. (Remote sensing letters, 2022)
A lidar-derived canopy height profile (CHP), generated from canopy bulk density (CBD) estimates for a sequence of 1-m increments through the canopy, provides a physical measure of forest structure. Measurement of physical properties are intuitively understandable and thus facilitate the use of lidar for investigating hypotheses regarding avian resource use. We illustrate the use of lidar-derived physical measures to explore the hypothesis that golden eagles (Aquila chrysaetos) prefer an open understory, which potentially aids visual identification of prey. Two golden eagles fitted with GPS tracking devices overwintered in the New Jersey Pinelands National Preserve. We generated CHPs from discrete-return lidar data for an area occupied by the birds. We compared the CHPs of sites the birds occupied to the surrounding available habitat and found that the occupied sites were significantly lower in CBD from the ground up to 5 m for perched/stationary birds, and from the ground up to 8 m for birds in flight. These results could be used by forest resource managers for promoting golden eagle habitat through prescribed fire. In addition, these results demonstrate the power of lidar to generate physically and intuitively meaningful measures of forest structure.